Treatment Adherence of Anti-TNF Drugs in the Patients with Inflammatory Bowel Disease: A Scale Development Study - Başak, Nur; Özgürsoy Uran, Berna Nilgün; Sarıtaş Yüksel, Elif (Turkish Journal of Gastroenterology, 2022)
Background: This work studies the validity and reliability of the Anti-TNF Alpha Treatment Adherence Scale, which has newly been developed to measure the compliance of inflammatory bowel disease patients using the anti-TNF alpha agents that are widely used in gastroenterology and rheumatology clinics. Methods: The study group consisted of 165 irritable bowel disease patients aged 18 years and above who were using anti-TNF alpha drugs. After creating a question pool with 40 items, the pilot study was applied with 70 patients. SPSS 25.0 and AMOS programs were used. Item-total correlation coefficients, Cronbach’s alpha and test-retest analysis, missing data, extreme value, normality, 27% sub- upper item discrimination analysis, and exploratory and confirmatory factor analyses were used. Results: The factor structure of the scale was examined with exploratory and confirmatory factor analyses and the contribution of these components to the total variance was measured as 74.21%. The Anti-TNF Alpha Treatment Adherence Scale was found in relation to the scale structure consisting of 12 items and 4 sub-dimensions. According to the first level multifactorial analysis results, the goodness of fit identities of the scale were found at an acceptable level, with the following values: RMSEA 0.067; GFI 0.92; AGFI 0.87; CFI 0.95; andχ2 79.876 (P = .000). Conclusion: It was determined that the Anti-TNF Alpha Treatment Adherence Scale represents the area to be measured, measures the researched structure, has a high internal consistency between items, is interrelated, and is consistent over time. As a result of all mea- surements, it was determined that it is a valid and reliable scale. Cite this article as: Başak N, Özgürsoy Uran BN, Sarıtaş Yüksel E. Treatment adherence of anti-TNF drugs in the patients with inflammatory bowel disease: A scale development study. Turk J Gastroenterol. 2022;33(4):336-345.